Analisis Profitabilitas, Firm Size, Business Risk dan Asset Tangibility Terhadap Komposisi Struktur Modal - Muktiadji, Nusa; Setiana, Anna; Deviena, Cinthia (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
The decision of financing closely related to the type of source of funds that will be used. Such decision must take into consideration whether the firm will be using internal or external source of funds. The purpose of this study is to analyse profitability as measured by the Operating Profit Margin (OPM), firm size, and determine business risk on the composition of the capital structure measured by Debt to Equity Ratio (DER). The methods used in this research are descriptive comparative and statistic analyses. These methods are used to answer the research questions on profitability analysis, firm size, business resik and asset tangibility and their influence on firm 's capital structure. Keywords: Profitability, Firm Size, Business Risk, Asset Tangibility, Composition of capital Structure.